SUCCESSFUL TREATMENT OF IATROGENIC INJURY TO EXTRAHEPATIC COMMON BILE DUCTS AFTER LAPAROSCOPIC CHOLECYSTECTOMY, WITH SEVERE COMPLICATIONS IN CONDITIONS PROVINCIAL DISTRICT HOSPITAL - Makhmudov, A.Kh.; Khujamuradov, B.R.; Mukhtarov, Kh.A.; Muradov, M.E.; Samiev, M.B. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
This article describes case of iatrogenic injury to extrahepatic common bile ducts during laparoscopic cholecystectomy with severe course (generalized biliary peritonitis) due to late diagnosis, hepatico-jujenal anastomosis (Roux-Y) was performed on a patient. However, due to failure anastomotic suture patient developed purulent-bile-fecal peritonitis. Redo surgery for HJA Roux-Y was performed with some technical difficulties: transmezacolon invaginative HJA by Roux-Y and annular drainage of intrahepatic bile duct by method of “skin-liver-transplantat”where the drainage passed from all above mentioned organs. As result of comprehensive treatment patient recovered.